2022
DOI: 10.3389/fpubh.2021.803815
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Care Activities (SASS-14) in Depression (PHQ-9): Evidence From Slovakia During the COVID-19 Pandemic

Abstract: In the ongoing situation, when the world is dominated by coronavirus disease 2019 (COVID-19), the development of self-care programs appears to be insufficient, while their role in mental health may be crucial. The aim of the study was to evaluate the associations between self-care activities and depression in the general Slovak population, but also in its individual gender and age categories. This was achieved by validating the self-care screening instrument, assessing differences, and evaluating the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…During the second wave, both groups of parents experienced higher levels of anxiety, stress, and depression, but the prevalence was significantly higher in parents of autistic children. Deterioration in the mental health of adults was similarly reported in neighboring European countries [6][7][8][9][10] and in research focusing on parents of children with ASD [25,26]. Insufficient or unclear information was the most prevalent stressor for both groups of parents in our study, which is fitting to the way pandemic rules were being officially announced and how they changed rapidly and unexpectedly at the time.…”
Section: Second Wavesupporting
confidence: 80%
See 2 more Smart Citations
“…During the second wave, both groups of parents experienced higher levels of anxiety, stress, and depression, but the prevalence was significantly higher in parents of autistic children. Deterioration in the mental health of adults was similarly reported in neighboring European countries [6][7][8][9][10] and in research focusing on parents of children with ASD [25,26]. Insufficient or unclear information was the most prevalent stressor for both groups of parents in our study, which is fitting to the way pandemic rules were being officially announced and how they changed rapidly and unexpectedly at the time.…”
Section: Second Wavesupporting
confidence: 80%
“…The results of our research must be interpreted with regard to its limits, especially that it was a series of three cross-sectional studies as opposed to a longitudinal research, and data were collected online via self-report methods. This also led to the predominance of females in our sample, which could have affected our results, since in other studies [5,6,8] women reported more severe mental health issues during the COVID-19 pandemic. On the other hand, following the development of a situation in the same country over a two years period and three pandemic waves while focusing on the same particular research population is the greatest strength of this study.…”
Section: Third Wavementioning
confidence: 87%
See 1 more Smart Citation
“…Depression has been found to be associated with dysfunction of the frontal lobe of the brain, the area responsible for executive functioning, a set of skills that involves reasoning, judgment, flexible thinking, emotional control, emotional judgment, self-monitoring, and problem-solving (Serani, 2017). Therefore, it is not surprising that individuals suffering from depression find it difficult to care for themselves; a growing body of evidence indicates that poor self-care can be a consequence of depression (Gavurova et al, 2022; Glowiak, 2020). People with poor self-care ability are more likely to develop or spread COVID-19; this patient lives with depression and was prone to poor self-care.…”
Section: Psychological Assessmentmentioning
confidence: 99%